THE TRIPOD: A RARELY MENTIONED FURNITURE TYPE (Innovation in Woodworking Industry and Engineering design, 2026)
In the article, a rarely mentioned in publications furniture type is considered: the tripod. The functional and symbolic meaning of this ancient artefact are researched aiming at revealing its role for the emergence of other furniture types in the XVIIIth, XIXth and XXth C because of the Antique Vogue and the trend for commodity search. Such objects, as stands, tables, trays, tea-tables, etc., are considered. In the process of this research, the role of this ancient archetype is revealed for the creation of modern products with a folding tripod structure, e.g., portable stools, tables, stands, etc.